Diagnosis and Management of Enthesopathy - Hafiziani; Najirman (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Enthesopathy is inflammation of the enthesis. Outcome Measures in Rheumatologic Clinical Trials (OMERACT) defined enthesopathy as abnormal hypoechoic (loss of normal fibrillar architecture) and/or tendon or ligament thickening at the site of bone attachment (sometimes containing hyperechoic foci that resemble calcifications) seen in two perpendicular planes on Doppler and/or bony changes including ensophytes, erosions, and irregularities. The causes of enthesopathy are categorized into two, namely, non-inflammatory causes and inflammatory causes. Non-inflammatory causes include trauma, degenerative, autoimmune, genetic, and metabolic. The causes of inflammation areas in seronegative spondyloarthropathy.